2021
DOI: 10.3390/jof7050393
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Fludioxonil Action Is Different to Osmotic Stress Sensing

Abstract: The group III two-component hybrid histidine kinase MoHik1p in the filamentous fungus Magnaporthe oryzae is known to be a sensor for external osmotic stress and essential for the fungicidal activity of the phenylpyrrole fludioxonil. The mode of action of fludioxonil has not yet been completely clarified but rather assumed to hyperactivate the high osmolarity glycerol (HOG) signaling pathway. To date, not much is known about the detailed molecular mechanism of how osmotic stress is detected or fungicidal activi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The HHKs are the primary sensor proteins of the signaling cascade, with variable sensory domains at the N-terminus (e.g. HAMP or HAMP-like linker domains (poly-HAMP)), an HK domain with an autophosphorylation site [147] [148] [149] and a Histidine similar ATPase catalytic domain (HATPase domain). The C-terminal response regulator domain (REC) within the HHK contains the Asp phosphoacceptor residue [149].…”
Section: Multistep Phosphorelay Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HHKs are the primary sensor proteins of the signaling cascade, with variable sensory domains at the N-terminus (e.g. HAMP or HAMP-like linker domains (poly-HAMP)), an HK domain with an autophosphorylation site [147] [148] [149] and a Histidine similar ATPase catalytic domain (HATPase domain). The C-terminal response regulator domain (REC) within the HHK contains the Asp phosphoacceptor residue [149].…”
Section: Multistep Phosphorelay Systemsmentioning
confidence: 99%
“…The phosphotransfer, for example, in the HKK Nik1p in C. albicans occurs from aa H510 within the HisKA domain to aa D924 within the REC domain [153] [154]. The His-Asp phosphorylation pattern within a HKK in M. oryzae is located at aa position H736 in the HisKA domain [147] [133] [149], and the phosphoryl group is transferred to the phosphoacceptor at position D1153 in the REC domain [155]. The aa position His69 is predicted to play an important role in the phosphoryl transfer activity of the HPt domain within the phosphotransfer protein Ypd1p in C. albicans [145] [156].…”
Section: Multistep Phosphorelay Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fludioxonil belongs to the phenylpyrrole group of fungicides with a broad antifungal spectrum. It is used to control a variety of plant-pathogenic fungi [ 1 , 2 , 3 , 4 ]. Previous studies have revealed that fludioxonil acts as a fungicide through the inhibition of Nik1 orthologs or Group III hybrid histidine kinase (HHK3), which leads to the improper activation of the p38/HOG MAPK pathway in fungal pathogens [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four articles investigated the effect of osmotic stress on sensing. The relationship between external osmotic stress sensing and the fungicidal activity of phenylpyrrole fludioxonil was the subject of a study by Bersching and Jacob [ 4 ]. Essential to both processes seems to be a group III two-component hybrid histidine kinase.…”
mentioning
confidence: 99%